A method for recovering phosphorus from sludge carbonized particles

Through membrane separation technology combined with EDTA pretreatment, the simultaneous dissolution of heavy metals and phosphoric acid ions in sludge pellets is solved, and the efficient removal of heavy metals and the improvement of phosphorus recovery rate is achieved, providing an efficient phosphorus recovery method for sludge pellets is provided.

CN118270743BActive Publication Date: 2024-12-31SHANDONG HUAYI ENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410378737.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2024-12-31
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

In the prior art, when the phosphoric acid ions are recovered by acid rinsing in sludge ions, heavy metal elements will be dissolved at the same time, making it difficult to effectively remove heavy metals and reduce the phosphorus recovery rate.

Method used

Using membrane separation technology, heavy metal ions were first seized with PES nanomembrane, then phosphate ions were seized with polyethersulfone nanomembrane, and EDTA was added to the filtrate for pretreatment. High-efficiency phosphorus recovery products were obtained by filtration and concentration of multi-layer membranes.

Benefits of technology

It effectively removes heavy metal ions in the acid leachate, improves the recovery rate of phosphate ions, significantly improves the quality and efficiency of phosphorus recovery products, and has broad application prospects and economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a phosphorus recovery method for sludge carbonized particles, and belongs to the technical field of sludge treatment. The phosphorus recovery method for sludge carbonized particles provided by the present application comprises the following steps: 1) treating the sludge carbonized particles by an acid leaching method, and collecting the leaching liquid; 2) passing the obtained leaching liquid through a first nano-membrane, and collecting the filtrate; 3) passing the obtained filtrate through a second nano-membrane, and collecting the retained liquid; 4) concentrating the retained liquid to obtain a phosphorus recovery product; the pore size range of the first nano-membrane in step 2) is 5 to 15 nm, and the pore size range of the second nano-membrane in step 2) is 0.1 to 0.5 nm. The phosphorus recovery method for sludge carbonized particles provided by the present application can effectively remove heavy metal ions dissolved in the acid leaching liquid, such as lead ions and copper ions with a high content in the sludge, and can effectively collect phosphate ions, thereby increasing the yield of phosphorus recovery products while reducing the heavy metal elements therein, and facilitating the subsequent application of phosphorus recovery products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for recovering phosphorus from sludge carbonized particles, belonging to the technical field of sludge treatment. Background Art

[0002] Phosphorus exists only in a bound state in nature, usually in the form of phosphate. Phosphate is non-renewable and most of it is obtained from phosphate rock. The long-term supply of phosphate rock depends on the availability of the deposits and the economic feasibility of their technical utilization. The global demand for phosphorus resources is growing steadily. The decline in the quality of raw phosphorus in sedimentary ores is a major issue because it contains toxic heavy metals and radionuclides. As an important strategic resource, phosphorus needs to be considered for recycling.

[0003] As a product of sewage treatment, sludge concentrates 30% to 50% of pollutants in sewage and has the dual attributes of pollution and resource. The safe treatment, disposal and resource utilization of sludge have always been an international research hotspot in the field of sewage treatment. Municipal sewage and sludge contain a large amount of phosphorus resources.

[0004] In the prior art, wet chemical methods, thermal chemical methods and other processes have been developed to recover phosphorus from sewage sludge, sludge liquid and sewage sludge ash. Among them, phosphorus recovery mostly adopts wet chemical methods, such as the precipitation process to recover magnesium ammonium phosphate. The wet chemical method can usually recover 5% to 30% of the phosphorus in the sewage treatment plant influent. Because in most cases only part of the phosphorus in the sludge liquid is recovered, this method has the advantages of relatively simple implementation and low cost, and has good plant absorption as a nitrogen and phosphorus fertilizer. Among them, the thermal treatment process is relatively more complex in technology and relatively more expensive than the wet chemical precipitation process, but this method can make the phosphorus recovery rate in the sewage treatment plant influent as high as 90% or more, and can burn the organic pollutants in the sewage sludge during the sewage sludge incineration process. The heat generated by the incineration process can also be recycled, for example, for high-temperature carbonization of the sludge.

[0005] Sludge carbonization is a sludge stabilization process that involves pyrolysis treatment under anaerobic or anoxic conditions to obtain carbon-containing solid products as the main target product. Organic matter will decompose during the carbonization process, and the products include pyrolysis gas composed of low-molecular organic matter, water vapor, etc., tar, and solid carbides mainly composed of fixed carbon and inorganic matter. Due to the evaporation of water and the volatilization of pyrolysis gas, sludge carbonization with developed surface and internal pores and rich in fixed carbon is gradually formed. Sludge carbonization has good stability in biology, chemistry, physics and other aspects, and has good prospects for resource utilization in many fields.

[0006] However, although the incinerated sewage sludge ash or carbonized sludge particles are rich in phosphorus and can be dissolved by acid leaching, heavy metals will also be dissolved at the same time. Therefore, how to effectively remove the dissolved heavy metal elements and obtain a higher phosphate ion recovery rate is a technical problem that urgently needs to be solved. Summary of the invention

[0007] In order to solve the above problems, a phosphorus recovery method of sludge carbonized particles is provided, which can effectively remove heavy metal ions dissolved in the acid leaching solution, such as lead ions and copper ions with high content in the sludge, and can effectively collect phosphate ions, thereby improving the yield of phosphorus recovery products and reducing heavy metal elements therein, thereby facilitating the subsequent application of phosphorus recovery products.

[0008] The present application provides a method for recovering phosphorus from sludge carbonized particles, the method comprising the following steps:

[0009] 1) Treating the sludge carbonized particles by acid leaching and collecting the leaching liquid;

[0010] 2) passing the obtained eluent through a first nano-membrane to collect a filtrate;

[0011] 3) passing the obtained filtrate through a second nano-membrane to collect the retentate;

[0012] 4) concentrating the retentate to obtain the phosphorus recovery product;

[0013] The pore size of the first nanofilm in step 2) is in the range of 5 to 15 nm, and the pore size of the second nanofilm in step 2) is in the range of 0.1 to 0.5 nm.

[0014] Optionally, in step 2), the pH range of the solution is controlled to be 3.0 to 4.0.

[0015] Optionally, in step 3), the pH range of the solution is controlled to be 6.5 to 7.0.

[0016] Optionally, in step 2), the operating pressure is controlled in the range of 30 to 50 bar.

[0017] Optionally, in step 3), the operating pressure is controlled in the range of 15 to 25 bar.

[0018] Optionally, in step 2), the first nanomembrane is a nanofiltration membrane, and the nanofiltration membrane is selected from one of a PES membrane, a PP membrane, a PTFE membrane, and a PEEK membrane.

[0019] Optionally, the nanofiltration membrane is selected from a PES membrane.

[0020] Optionally, in step 3), the second nano-membrane is a weakly acidic ion exchange membrane, and the weakly acidic ion exchange membrane is selected from one of a phenyl ether sulfone group membrane, a phenol-formaldehyde resin membrane, and a polyether sulfone membrane.

[0021] Optionally, the nanofiltration membrane is selected from polyethersulfone membrane.

[0022] Optionally, between step 2) and step 3), there is also a step of adding EDTA to pretreat the filtrate obtained in step 2), the pH in the reaction conditions is controlled at 4.0-6.0, and the pretreated filtrate is obtained by removing the complex precipitate after filtration, and then the pretreated filtrate is subjected to the treatment operation in step 3).

[0023] The beneficial effects of this application include but are not limited to:

[0024] 1. According to the phosphorus recovery method of sludge carbonized particles of the present application, membrane separation technology is used and PES membrane and polyethersulfone membrane are successively adopted in combination, wherein the PES membrane can effectively retain heavy metal ions and allow phosphate ions to pass through, and the polyethersulfone membrane can effectively retain phosphate ions, thereby obtaining a retentate containing phosphate ions, and a phosphorus recovery product is obtained after concentration treatment.

[0025] 2. According to the phosphorus recovery method of sludge carbonized particles of the present application, a higher phosphorus yield can be obtained while effectively removing heavy metal ions therein. The process for obtaining phosphorus recovery products by treating sludge carbonized particles provided in the present application has broad application prospects and economic value in the field of phosphorus recovery from sludge carbonized particles.

[0026] 3. According to the phosphorus recovery method of sludge carbonized particles of the present application, by adding EDTA to the filtrate for pretreatment before polyethersulfone membrane filtration treatment, it is possible to further reduce the heavy metal ions in the phosphorus recovery product and improve the phosphate ion retention rate during the polyethersulfone membrane filtration treatment, thereby significantly improving the efficiency of phosphorus recovery. DETAILED DESCRIPTION

[0027] The present application is described in detail below in conjunction with examples, but the present application is not limited to these examples. Unless otherwise specified, the raw materials and catalysts in the examples of the present application are purchased through commercial channels.

[0028] Example 1

[0029] The sludge carbonized particles obtained after the carbonization treatment are treated by an acid leaching method to obtain a leaching liquid. The acid leaching method can be carried out in a manner commonly used in the art. For example, in this embodiment, a 10% hydrochloric acid solution is used to soak the sludge carbonized particles, and the agitator is started and the leaching is carried out under stirring to fully mix the hydrochloric acid and the sludge carbonized particles. Then, the solid particles and the acid solution are separated by filtration to obtain a leaching liquid.

[0030] The eluent is filtered through the first nano-membrane, so that the phosphate ions in the eluent flow through, while heavy metal ions such as copper ions and lead ions are retained. The first nano-membrane uses a PES membrane with a pore size range of 5 to 15 nm. The operating pressure range is controlled to be 30 to 50 bar during the filtration process, and the pH range of the solution is controlled to be 3.0 to 4.0 by adding a hydrochloric acid solution during the filtration process. After the filtration is completed, the filtered flow-through liquid is collected to obtain a filtrate.

[0031] The obtained filtrate is subjected to EDTA pretreatment. First, hydrochloric acid solution is added to adjust the solution pH range to between 4.0 and 6.0, and after adding EDTA, it is left to stand for 30 minutes to 2 hours for complexation reaction to occur, and the complexation precipitate is removed by filtration to obtain the pretreated filtrate.

[0032] The pretreated filtrate is filtered through a second nano-membrane to retain phosphate ions in the filtrate. The second nano-membrane uses a polyethersulfone membrane with a pore size range of 0.1 to 0.5 nm. The operating pressure range is controlled to be 15 to 25 bar during the filtration process, and the pH range of the solution is controlled to be 6.5 to 7.0 during the filtration process. After the filtration is completed, the retentate is collected and concentrated to obtain a phosphorus recovery product.

[0033] Experimental Example 1 Selection of separation membrane

[0034] 1) Selection of the first nanofilm

[0035] In order to explore the effects of different first nanomembranes on the removal of heavy metal ions and the retention of phosphate ions, the experimenters mainly investigated several common nanofiltration membranes, including PES membrane, PP membrane, PTFE membrane and PEEK membrane. The results of metal ion retention rate and phosphate ion permeability are shown in the following table.

[0036] Table 1 First nanofilm screening results

[0037] The first nanofilm Lead ion retention rate (%) Copper ion retention rate (%) Phosphate ion permeability (%) PES membrane 85.3 80.1 76.4 PP film 50.7 83.3 75.3 PTFE membrane 38.9 81.2 67.4 PEEK membrane 75.8 49.0 58.7

[0038] According to the results in Table 1, when the PES membrane is used as the first nanomembrane, it has the best retention effect on lead ions and copper ions, can effectively remove heavy metal ions in the pickling solution, and maintain a good permeability of phosphate ions. However, other nanofiltration membranes are not suitable as the first nanomembrane in the membrane separation technology of this scheme.

[0039] 2) Selection of the second nanofilm

[0040] In order to further explore the effect of different second nanomembranes on the retention of phosphate ions, the experimenters mainly investigated several common ion exchange membranes, including weakly acidic ion exchange membranes, phenyl ether sulfone group membranes, phenol-formaldehyde resin membranes and polyether sulfone membranes.

[0041] Table 2 Second nanofilm screening results

[0042] The second nanofilm Phosphate ion retention rate (%) Phenyl ether sulfone group membrane 52.8 Phenol-formaldehyde resin film 81.2 Polyethersulfone membrane 84.7

[0043] According to the results in Table 2, when the polyethersulfone membrane is used as the second nanomembrane, a good phosphate ion retention rate can be obtained, while the phosphate ion retention effect of other weakly acidic ion exchange membranes is poor, resulting in low efficiency of phosphorus recovery.

[0044] Experimental Example 2 Optimization of Filtration Conditions

[0045] After determining the selection of the first and second nanomembranes, the experimenters continued to optimize the working conditions of the two nanomembranes, specifically examining and screening the optimal pH conditions and operating pressures.

[0046] 1) First nanofilm working conditions

[0047] Based on the PES membrane selected in Experimental Example 1, the conditions of pH ranges of 1.0-2.0, 2.0-3.0, 3.0-4.0, and 4.0-5.0 were further investigated. The results of the heavy metal ion retention rate and phosphate ion permeability are shown in the following table.

[0048] Table 3 Results of the first nanomembrane pH working condition screening

[0049] pH conditions Lead ion retention rate (%) Copper ion retention rate (%) Phosphate ion permeability (%) 1.0~2.0 83.6 78.2 43.8 2.0~3.0 89.2 67.3 83.1 3.0~4.0 88.2 85.8 80.7 4.0~5.0 74.0 56.2 73.9

[0050] According to the results in Table 3, the optimal working pH range of the first nanomembrane is 3.0-4.0. Within this range, lead ions and copper ions are efficiently retained, while most phosphate ions are able to pass through. When the pH range is 3.0-4.0, the permeability of phosphate ions can be significantly improved, thereby improving the phosphorus recovery efficiency.

[0051] After determining the optimal working pH range of the first nanomembrane, the experimenters continued to investigate the effect of operating pressure. The results are shown in the following table.

[0052] Table 4 First nanomembrane working pressure screening results

[0053]

[0054] According to the results in Table 4, for the first nanomembrane, when the working pressure is 30-50 bar, a higher phosphate ion permeability can be obtained while a better heavy metal ion retention effect can be obtained. The experimenters found that the time consumption is also shorter at this time, which can improve the filtration efficiency.

[0055] 2) Second nanofilm working conditions

[0056] Based on the polyethersulfone membrane selected in Experimental Example 1, the conditions of pH 5.0-5.5, 5.5-6.0, 6.0-6.5, and 6.5-7.0 were investigated respectively. The results of phosphate ion rejection are shown in the following table.

[0057] Table 5 Results of screening the pH working conditions of the second nanomembrane

[0058] pH conditions Phosphate ion retention rate (%) 5.0~5.5 81.4 5.5~6.0 82.9 6.0~6.5 84.2 6.5~7.0 89.5

[0059] According to the results in Table 5, the optimal working pH range of the second nanomembrane is 6.5-7.0, within which phosphate ions can be efficiently retained.

[0060] After determining the optimal working pH range of the second nanomembrane, the experimenters continued to investigate the effect of operating pressure. The results are shown in the following table.

[0061] Table 6 Second nanofilm working pressure screening results

[0062] Operating pressure(bar) Phosphate ion retention rate (%) 5~15 95.8 15~25 97.3 25~35 85.2 35~45 83.8 45~55 80.7

[0063] According to the results in Table 6, for the second nano-membrane, a better phosphate ion rejection rate can be obtained when the operating pressure ranges from 15 to 25 bar.

[0064] Experimental Example 3 Investigation of Nanofilm Thickness

[0065] After determining the selection of the first nanomembrane and the second nanomembrane and their respective working conditions, the experimenters finally examined the thickness conditions of the nanomembrane.

[0066] 1) Investigation of the thickness of the first nanofilm

[0067] The experimenters investigated the thickness range of 10 / 50 / 100 / 200 nm and their effects on the retention rate of heavy metal ions and the transmittance of phosphate ions. The results are shown in the table below.

[0068] Table 7 Results of the first nanofilm thickness investigation

[0069]

[0070]

[0071] According to the results in Table 7, when the thickness of the first nanofilm is within the range of 50 to 100 nm, a good heavy metal ion removal effect can be obtained and a high phosphate ion permeability can be maintained.

[0072] 2) Investigation of the thickness of the second nanofilm

[0073] The experimenters investigated the thickness range of 100 / 150 / 200 / 250 / 300 nm and their effects on the retention rate of phosphate ions. The results are shown in the following table.

[0074] Table 8 Results of investigation on the thickness of the second nanofilm

[0075] Thickness(nm) Phosphate ion retention rate (%) 100 92.6 150 96.4 200 97.5 250 98.2 300 98.7

[0076] According to the results in Table 8, when the thickness of the second nanofilm is between 150 and 300 nm, a higher phosphate ion interception effect can be obtained.

[0077] Experimental Example 4 Metal Precipitant Pretreatment

[0078] Since some heavy metal ions still pass through the first nanomembrane and enter the filtrate after treatment with the first nanomembrane, in order to further remove the heavy metal ions in the phosphorus recovery product, the experimenters added EDTA to the collected retentate after treatment with the second nanomembrane and before concentration to complex the residual metal ions, remove them by filtration, and then concentrate them.

[0079] During the experiment, the experimenters found that if the filtrate treated with the first nanomembrane was pretreated with EDTA before the second nanomembrane treatment, it would not only effectively reduce the heavy metal ions in the final phosphorus recovery product, but also significantly increase the phosphate ion retention rate after the second nanomembrane treatment, thereby greatly improving the phosphorus recovery efficiency. The experimenters found that the removal efficiency of residual heavy metal ions by adding EDTA was greatly affected by pH. The heavy metal ions after complexation and precipitation could be removed by filtration. When the second nanomembrane treatment was carried out afterwards, the phosphate ion retention efficiency was also significantly improved. The experimental results are shown in the following table.

[0080] Table 9 EDTA pretreatment results at different pH

[0081] pH conditions Residual heavy metal ion removal rate (%) Phosphate ion retention rate (%) 3.0~4.0 47.9 89.9 4.0~5.0 95.2 97.8 5.0~6.0 95.0 98.8 6.0~6.5 66.8 93.1 6.5~7.0 73.6 86.4

[0082] According to the results in Table 9, when EDTA is added to pretreat the filtrate and the pH range of the filtrate is adjusted between 4.0 and 6.0, a higher residual heavy metal ion removal effect is achieved, and a higher phosphate ion retention rate can be maintained here.

[0083] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for recovering phosphorus from sludge carbonized particles, characterized in that: The method comprises the following steps: 1) Treating the sludge carbonized particles by acid leaching and collecting the leaching liquid; 2) passing the obtained eluent through a first nano-membrane and collecting a filtrate; 3) passing the obtained filtrate through a second nano-membrane to collect the retentate; 4) concentrating the retentate to obtain the phosphorus recovery product; In step 2), the first nano-membrane is a PES membrane, the pore size of the first nano-membrane in step 2) is in the range of 5 to 15 nm, the thickness of the first nano-membrane in step 2) is in the range of 50 to 100 nm, the pH of the solution in step 2) is controlled in the range of 3.0 to 4.0, and the operating pressure in step 2) is controlled in the range of 30 to 50 bar; The second nano-membrane in step 3) is a polyethersulfone membrane, the pore size of the second nano-membrane in step 3) is in the range of 0.1 to 0.5 nm, the thickness of the second nano-membrane in step 3) is in the range of 150 to 300 nm, the pH of the solution in step 3) is controlled in the range of 6.5 to 7.0, and the operating pressure in step 3) is controlled in the range of 15 to 25 bar; The step between step 2) and step 3) also includes the step of adding EDTA to pretreat the filtrate obtained in step 2), the pH in the reaction conditions is controlled at 4.0-6.0, the complex precipitate is removed after filtration to obtain the pretreated filtrate, and then the pretreated filtrate is subjected to the treatment operation in step 3).